Mezinárodní rok míru, 1986 - Somek, L (Ceskoslovensky Mirovy Vybor v Nakladatelstvi Svoboda, 1985)
Logo of the International Year of Peace in white, over blue background Suggested translation: International Year of Peace, 1986 PO-0308